Pain Assessment Using Virtual Reality Facemask During Bone Marrow Aspiration: Prospective Study Including Propensity-Matched Analysis - Lou Soret; Nicolas Gendron; Nadia Rivet; Richard Chocron; Laure Macraigne; Darless Clausse; Bernard Cholley; Pascale Gaussem; David M Smadja; Luc Darnige (JMIR Publications, 2022)
BackgroundBone marrow aspiration (BMA) is a medical procedure necessary to the diagnosis and monitoring of patients with hematological or nonhematological disorders. This procedure is considered painful, and patients are generally anxious before and during BMA. ObjectiveThis study assesses the effect of immersive virtual reality on pain during BMA. MethodsThis observational prospective and monocentric study enrolled 105 consecutive patients who underwent sternal BMA with lidocaine anesthesia. The study was carried on during 2 periods. First, virtual reality facemask (VRF) was proposed to all patients in the absence of exclusion criteria. During the second period, BMA was performed without the VRF. For all patients, pain intensity after the procedure was assessed using a 10-point numerical pain rating scale (NPRS). All analyses were performed on propensity score-matched cohort (with or without VRF) to evaluate efficacy on NRPS levels. ResultsThe final matched cohort included 12 patients in the VRF group and 24 in the control group. No difference in anxiety level before BMA evaluated by the patient and by the operator was observed between groups (P=.71 and .42 respectively). No difference of NPRS was observed using VRF when compared to control group (median NPRS 3.8, IQR 2.0-6.3 vs 3.0, IQR 1.9-3.0, respectively; P=.09). ConclusionsOur study did not prove the efficacy of VRF to reduce pain during BMA.